Analysis of functional domain organization in DNA topoisomerase II from humans and Saccharomyces cerevisiae. - Jensen, S (1996)
The functional domain structure of human DNA topoisomerase IIalpha and Saccharomyces cerevisiae DNA topoisomerase II was studied by investigating the abilities of insertion and deletion mutant enzymes to support mitotic growth and catalyze transitions in DNA topology in vitro. Alignment of the human topoisomerase IIalpha and S. cerevisiae topoisomerase II sequences defined 13 conserved regions separated by less conserved or differently spaced sequences. The spatial tolerance of the spacer regions was addressed by insertion of linkers. The importance of the conserved regions was assessed through deletion of individual domains. We found that the exact spacing between most of the conserved domains is noncritical, as insertions in the spacer regions were tolerated with no influence on complementation ability. All conserved domains, however, are essential for sustained mitotic growth of S. cerevisiae and for enzymatic activity in vitro. A series of topoisomerase II carboxy-terminal truncations were investigated with respect to the ability to support viability, cellular localization, and enzymatic properties. The analysis showed that the divergent carboxy-terminal region of human topoisomerase IIalpha is dispensable for catalytic activity but contains elements that specifically locate the protein to the nucleus.